Analisis Pola Asuh Demokratis, Otoriter, dan Permisif terhadap Perkembangan Sosial-Emosional Anak Usia Dini - Ijar Salna; Lu’lu Rahmadanti; Aulia Fitriani Munthe (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Parents act as early educators entrusted with guiding, nurturing, and caring for their children. Their influence is crucial from the outset, as they substantially shape their children's character and disposition. The way parents parent their children can significantly enhance their overall development, as their methods significantly influence their children's social and emotional maturity. To foster healthy maturation and ensure their children's social integration, parents need to thoroughly understand the intricacies of their children's social and emotional development. Parents are the first teachers responsible for teaching, nurturing, and raising their children. Parental involvement is crucial. This study aims to examine the significance of parenting strategies employed by mothers and fathers and the extent to which these strategies shape their children's social and emotional development. The results of this study identified three distinct categories of parenting tactics commonly employed by mothers and fathers in raising their children: indulgent, dictatorial, and collaborative. Each of these parenting approaches exerts a unique influence on children's social and emotional maturation. The main difference lies in the observation that dictatorial and indulgent parenting approaches typically produce less beneficial results than collaborative parenting approaches, which typically produce more beneficial results. Therefore, it is recommended that mothers and fathers adopt a collaborative parenting approach when raising their children.